Peran Digitalisasi dalam Meningkatkan Kinerja Perbankan di Era Transformasi Teknologi - Indrayani, Eka; Berlian, Sucma; Lestari, Rina Puji; Purnomo, Rochmat Aldy (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This article aims to analyze the role of digitalization on banking performance, both in terms of operational efficiency, customer service, and bank competitiveness in the market. Digitalization has brought significant changes in various sectors, including the banking sector. The era of digital transformation encourages banks to adopt sophisticated information technology in their operations, which in turn affects banking performance. The rapid digital transformation in the banking world emphasizes the need for adaptation to digital services to meet customer needs effectively. This study uses the literature review method, which is an approach used to study, analyze, and summarize the results of existing research in the literature or sources that are relevant to the topic being studied. The results of the study show that digitalization has a significant impact on increasing operational efficiency, reducing operational costs, and improving the quality of service to customers. However, challenges such as personal data protection and cybersecurity are also major concerns in the implementation of digital technology in banking. In conclusion, digitalization is not only an opportunity, but also a challenge that must be managed properly to achieve optimal performance in the era of digital transformation